Applying genomic and transcriptomic advances to mitochondrial medicine - Macken, William L.; Vandrovcova, Jana; Hanna, Michael G.; Pitceathly, Robert D. S. (Nature reviews. Neurology, 2021)
Next-generation sequencing (NGS) has increased our understanding of the molecular basis of many primary mitochondrial diseases (PMDs). Despite this progress, many patients with suspected PMD remain without a genetic diagnosis, which restricts their access to in-depth genetic counselling, reproductive options and clinical trials, in addition to hampering efforts to understand the underlying disease mechanisms. Although they represent a considerable improvement over their predecessors, current methods for sequencing the mitochondrial and nuclear genomes have important limitations, and molecular diagnostic techniques are often manual and time consuming. However, recent advances in genomics and transcriptomics offer realistic solutions to these challenges. In this Review, we discuss the current genetic testing approach for PMDs and the opportunities that exist for increased use of whole-genome NGS of nuclear and mitochondrial DNA (mtDNA) in the clinical environment. We consider the possible role for long-read approaches in sequencing of mtDNA and in the identification of novel nuclear genomic causes of PMDs. We examine the expanding applications of RNA sequencing, including the detection of cryptic variants that affect splicing and gene expression and the interpretation of rare and novel mitochondrial transfer RNA variants. In this Review, the authors discuss the unique challenges involved in performing genetic testing for primary mitochondrial diseases and consider the value of advanced approaches such as long-read sequencing, RNA sequencing and the interpretation of transfer RNA variants. Key points At present, the diagnosis of primary mitochondrial disease is a multistep process often involving a number of time-consuming and highly manual molecular techniques. Early whole-genome sequencing of blood, analysing both mitochondrial and nuclear DNA, is likely to improve diagnostic efficiency in some people with mitochondrial disease. In future, the application of long-read sequencing to mitochondrial DNA could build on the advances made by next-generation sequencing to further enhance coverage, and enable the identification of large-scale rearrangements and point mutations in a single test. As with other rare diseases, whole-genome long-read sequencing might provide the next diagnostic uplift given its ability to identify structural variants, short tandem repeat variants and epigenetic modifications, and to phase compound heterozygous variants. Mitochondrial medicine is poised to benefit substantially from the increasing use of RNA sequencing of tissue samples; advances in pre-processing and sequencing of transfer RNA are enabling new insights into this molecule, which plays an outsized role in the aetiology of mitochondrial diseases.